Alma caribe : Afro Cuban Jazz - Project (2016)
El programa está dedicado a Perfil: Cuban music group, plays a curious blend of guaracha, bolero, and traditional jazz filtered through some of Cuba's most respected native players. El programa está acompañado de las siguientes piezas musicales: Baila Mi Conga Vacílala - Interprete Afro-Cuban Jazz Project / Soy el Matancero - Interprete Afro-Cuban Jazz Project / Charanga Para Ti - Interprete Afro-Cuban Jazz Project / Changüi para Gozar - Interprete Afro-Cuban Jazz Project / Campiña - Interprete Afro-Cuban Jazz Project / Rumbatá - Interprete Afro-Cuban Jazz Project / Rumberos de Verdá - Interprete Afro-Cuban Jazz Project / Coge Este Tumbao - Interprete Afro-Cuban Jazz Project / Tu Mi Delirio - Interprete Afro-Cuban Jazz Project.